Divination among the Etche of Niger Delta - Amadi, Emmanuel Echezolochi; Kii, Pius Barinaadaa (NIU Journal of Humanities, 2025)
The unusual occurrences such as a tree or a branch falling down especially when there is no wind or rain, a sheep growing a horn, the appearing and disappearing of millipede and by extension frequent death, in explicable diseases, resulting in fear. However, form the basis of divination among Etche as a means to proffer solutions to the above circumstances. the paper posits that divination has helped to ascertain the underlying causes of these occurrences. The paper also argues that these occurrences not only portend messages from the supersensible realm but are also manifestations of the anger of the supersensible entities. The study adopted phenomenological approach to interpret and describe the causes of these usual signs. The study also adopts primary and secondary sources (primary sources-oral interviews; report of the custodians of Etche custom and tradition and handed down tradition and secondary sources (published materials). Findings reveal that divination among Etche is so significant not only in the religious life of the people, but also as a means to offer explanations to inexplicable circumstances. Keywords: Etche, Diviner and Divination.